A comprehensive comparison of the corrosion performance, fatigue behavior and mechanical properties of micro-alloyed MgZnCa and MgZnGe alloys. (5th January 2020) - Jiang, Pingli; Blawert, Carsten; Hou, Ruiqing; Bohlen, Jan; Konchakova, Natalia; Zheludkevich, Mikhail L.
Abstract: The fast and non-uniform corrosion of Mg alloys largely limits their practical applications in various fields. In present study, micro-alloyed extruded Mg0.5Zn0.2Ca and Mg0.5Zn0.2Ge alloys were developed to avoid the severe galvanic corrosion between Mg matrix and second phases. Corrosion behavior, mechanical integrity and fatigue behavior in two corrosive electrolytes of these two alloys were investigated. The results revealed a better short-term corrosion property for Mg0.5Zn0.2Ge alloy, but an improved long-term corrosion resistance for Mg0.5Zn0.2Ca alloy, resulting from the different protective abilities of surface layers and microstructures of the alloys. Although Mg0.5Zn0.2Ca alloy presented relatively lower strength owing to the weaker texture, it owned better mechanical integrity than Mg0.5Zn0.2Ge alloy due to the more uniform corrosion in salt spray, indicating the significant effect of localized corrosion on mechanical integrity of materials. Furthermore, the corrosion of the alloys in electrolytes decreased the fatigue resistance for both alloys, but Mg0.5Zn0.2Ca showed higher sensitivity to corrosive environments under cyclic loading. The comprehensive studies of these two alloys highlight the interactions between corrosion and mechanical integrity and/or fatigue behavior of materials and suggest the importance of the investigation of the overall properties when new Mg alloys are developed and evaluated for practical applications. Graphical abstract: Image 1 Highlights: The overall properties of a commonly studied MgZnCa and a rarely studied MgZnGe alloy are compared. Mg0.5Zn0.2Ge alloy exhibits a better short-term corrosion property while Mg0.5Zn0.2Ca alloy possesses better long-term one. Appearance of localized corrosion after specific period results in the varied mechanical integrity for the two alloys. The fatigue resistance of Mg0.5Zn0.2Ca alloy is more sensitive to aggressive environment.